Doing Business on the Internet. - Michaelson, Jennifer (Booklist, 2012)
The article reviews the second edition of the book "Gale E-commerce Sourcebook," edited by Virgil L. Burton, and the second edition of the book "Gale Encyclopedia of E-commerce," edited by Laurie J. Fundukian.